Detection of faulty accelerometer mounting from response measurements. (7th July 2020) - Randall, R.B.; Smith, W.A.
Abstract: Data integrity has become more critical with the growth in remote semi-automated machine health monitoring. The mounted resonance frequency of an accelerometer, if correctly mounted on a flat surface, is normally quite repeatable, for example at different locations on the same object. A method has recently been developed which largely separates forcing and transfer functions in response signals, by applying an exponential window in the cepstrum. This technique can show the resonance peaks in response spectra at all measurement points, and has been applied successfully in operational modal analysis. This paper proposes how this technique can be used to detect a faultily mounted accelerometer in industrial applications. Changes in the natural frequencies of the structure should show up equally in all measurements, but deterioration in the mounting condition of an individual accelerometer would only affect the mounted resonance frequency for that transducer. This paper demonstrates these principles using measurements on a gear test rig, operating with a range of different speed profiles, with two similar accelerometers, one having correct and then faulty mounting of two different severities. Measurements are also compared for accelerometers with a wider frequency range.